Optimizing Anti-Corruption Education in Higher Education: Enhancing Awareness and Promoting Action against Corruption among University Students - Witarsa, Witarsa (Yayasan Sembilan Pemuda Indonesia, 2023)
Corruption has become a pressing concern in Indonesia, penetrating various sectors of society. Tackling this issue, integrity education at the tertiary level has emerged as an underexplored strategic solution. This study aims to analyze the effectiveness and role of integrity education in fostering anti-corruption commitment among university students. A systematic literature review examines diverse integrity education strategies and implementations. Results indicate that integrity education positively influences individuals’ awareness and attitudes toward corrupt practices. Challenges, however, persist in fully integrating these concepts into curricula and promoting active student engagement. The main conclusion emphasizes the crucial role of integrity education in cultivating a resilient anti-corruption generation within universities. Implications encompass the need for interdisciplinary collaboration and partnerships to develop a comprehensive approach. Practical recommendations include innovative teaching methods and further research to assess integrity education’s impact on higher education. This study contributes to comprehending anti-corruption efforts through integrated integrity education within research limitations.